Localização das instalações de uma empresa de marketing jurídico digital na cidade de Mossoró: um estudo de caso - Bezerra Segundo, Gilmar Lopes (Universidade Federal Rural do Semi-Árido, 2020)
The allocation of a company's facilities is a long-term decision that directly influences the quality of the services provided. This type of decision requires an evaluation of a greater number of subjective requirements, making it more difficult to use more traditional decision models. Making use of a multicriteria method means that there is a situation where there are at least two alternatives to choose, and this choice is made with the purpose of achiving multiple objectives. This research aims to define the best place to set the company's facilities of a digital juridical marketing company in the city of Mossoró-RN. The study was conducted based on the PROMETHEE II method to assist in decision making. The location of the facilities must be a mandatory theme in the strategic planning of organizations, considering that this can provide in several competitive advantages for the organization. Defining the best location to set up a business means determining which location provides the greatest amount of benefits. This survey presents a ranking of possible alternatives, showing to the decision maker which properties provides the most benefits based on their needs.
Monografia
Keywords: Multicritério; PROMETHEE II; Alocação; Marketing; Allocation; ENGENHARIAS::ENGENHARIA DE PRODUCAO